Enhancing Resistance to Salinity in Wheat by Using Streptomyces sp. HU2014 - Hongxia Zhu; Linfeng Hu; Tetiana Rozhkova; Chengwei Li (Agronomy, 2023)
Salt stress affects the growth and global production of wheat (Triticum aestivum L.). Plant growth-promoting microbes can enhance plant resistance to abiotic stresses. In this study, we aimed to assess the inoculation of soil with Streptomyces sp. HU2014 to improve wheat tolerance to salt stress from multiple perspectives, including the interaction of the strain, the addition of NaCl, the condition of the wheat, and rhizosphere microbial communities. The results showed that the strain promoted wheat growth under NaCl stress by increasing biomass by 19.8%, total chlorophyll content by 72.1%, proline content by 152.0%, and malondialdehyde content by 106.9%, and by decreasing catalase by 39.0%, peroxidase by 1.4%, and soluble sugar by 61.6% when compared to the control. With HU2014 soil inoculation, total nitrogen, nitrate nitrogen, total phosphorus, and Olsen phosphorus increased, whereas ammonium nitrogen and pH decreased. HU2014 inoculation and/or the addition of NaCl affected the diversity of rhizosphere bacteria, but not fungi. The structure of the microbial community differed after HU2014 inoculation, with Proteobacteria, Acidobacteriota, Bacteroidota, and unclassified fungi being the dominant phyla, and these taxa correlated with the above-mentioned soil parameters. Thus, this study provided a promising way to enhance wheat tolerance to salt stress and improve the agricultural ecological environment by using plant growth-promoting microbes.